Urgensi Etika dan Budaya Antiplagiat Guna Membangun Integritas dalam Penerapan dan Pengembangan Ilmu Hukum - Haykal, Hassanain (Zenit, 2012)
Human as individual have their own self preservation or interest in living their own lives. Every single individual has a different interest, that can lead into a conflict. In order to minimalize a conflict, a person need a guideline or instruction called ethics. Ethics becomes very important thing for human-being, both in their interaction within the family, society and the formal environment as well, as education. Within formal education, especially higher education, where transfer of knowledge takes  place, lack of understanding of ethics will lead to a great conflict. Conflicts can appear in the form of acts of plagiarism committed by students, professors, researchers, and academic staff. Act of plagiarism shows weakness of integrity in the application and development of science. Consequently, the implementation of a comprehensive ethics-understanding, and efforts to foster a anti-plagiarism culture is urgently needed, especially in higher education environment. Keywords: ethical, cultural anti-plagiarism, integrity, knowledge